Effect of aging on dynamic postural stability and variability during a multi-directional lean and reach object transportation task. (September 2016) - Huntley, Andrew H.; Zettel, John L.; Vallis, Lori Ann
Highlights: Young and Older adults completed multi-directional object transport task. Older adults exhibited frontal plane stability decrements during low direction. Similar movement variability between age groups regardless stability decrement. Multi-directional object transport task reveals underlying deficits in Older Adults. Abstract: A "reach and transport object" task that represents common activities of daily living may provide improved insight into dynamic postural stability and movement variability deficits in older adults compared to previous lean to reach and functional reach tests. Healthy young and older, community dwelling adults performed three same elevation object transport tasks and two multiple elevation object transport tasks under two self-selected speeds, self-paced and fast-paced. Dynamic postural stability and movement variability was quantified by whole-body center of mass motion. Older adults demonstrated significant decrements in frontal plane stability during the multiple elevation tasks while exhibiting the same movement variability as their younger counterparts, regardless of task speed. Interestingly, older adults did not exhibit a tradeoff in maneuverability in favour of maintaining stability throughout the tasks, as has previously been reported. In conclusion, the multi-planar, ecologically relevant tasks employed in the current study were specific enough to elucidate decrements in dynamic stability, and thus may be useful for assessing fall risk in older adults with suspected postural instability.